Pesquisa-formação em uma escola da rede municipal de Santo André: o uso dos portfólios reflexivos na formação de professores - Souza, Denise Pereira Pedro (2022)
The object of the research study is the research-training developed through reflective portfolios with teachers from a municipal school in Santo André. The research sought to answer the following questions: What is the effectiveness of the use of reflective portfolios in teachers' in-service continuing education, in order to promote reflection on knowledge, teaching practices and professional development? Does the degree of involvement and participation of teachers in this research-training process allow us to say that a collaborative practice is built? The general objective of this research is to carry out a research-training and analyze it, having as main support the production of the participants via reflective portfolios. We went through the research path in order to try to reach the specific objectives, such as: understand, identify and characterize the knowledge of the teachers of this unit and their professional training; provide a collaborative training that dialogues with the doings of the educational practices; understand and establish a logic of professional development with the teachers, making use of reflective portfolios. Eight meetings were held during the second semester of 2021, four of which were used by the teachers to read and study the literature agreed upon individually, and the other four meetings were used for collective discussion. The participants of the collaborative research-training were the pedagogical assistant and seven elementary school teachers, who made use of the reflective portfolios. There were also two school managers and two guest teachers, and it is important to emphasize that they all participated voluntarily, totaling twelve participants between the two instruments of analysis: the reflective portfolios and the transcriptions of the speeches. For the meetings, texts of international authors that deal with curriculum, teachers' professional development, teachers' knowledge, and educational practices were selected. The meetings were recorded and transcribed. The audios of the meetings were also a source of data analysis. The theoretical framework and the analysis categories are based on authors who talk about reflective portfolios, teacher education, curriculum, teaching knowledge, educational practices and professional development: Idália Sá Chaves, Patrícia Aparecida Bioto, Michel Young, Maurice Tardif, Phillippe Perrenoud, Claude Lessard, Antoni Zabala, Donald Schön, Luciana Maria Giovanni, António Sampaio da Nóvoa, Paulo Freire. As results, it can be pointed out that the research-training developed is an enhancer of a training model that proposes the school as a locus of continuing education, based on practices that place teachers as active subjects in the search for a collaborative, democratic and emancipating culture.